Imaging findings in pediatric single‐sided deafness and asymmetric hearing loss. (27th May 2019) - Lipschitz, Noga; Kohlberg, Gavriel D.; Scott, Michael; Greinwald, John H.
Abstract : Objective: To examine the imaging findings on computer tomography (CT) and magnetic resonance imaging (MRI) in pediatric single‐sided deafness (SSD) and asymmetric hearing loss (ASH). Methods: The medical records of 189 pediatric patients with SSD and ASH were retrospectively reviewed, and imaging findings were compared. SSD was defined as unilateral profound hearing loss and contralateral normal hearing ear. In the ASH group, ASHw was defined as the worse hearing ear with profound hearing loss, while ASHb was defined as the better hearing ear with mild‐moderate hearing loss. Results: There were 170 patients with SSD and 19 patients with ASH. In the SSD group, 83 patients (48.8%) had imaging findings associated with hearing loss. In the ASH group, such imaging findings were found in six (31.6%) of the ASHw and in five (26.3%) of the ASHb ears. The most common finding in the SSD group was cochlear nerve deficiency (50.6%), followed by cochlear dysplasia (39.8%) and enlarged vestibular aqueduct (26.5%). In the ASH groups, cochlear dysplasia was seen in three (50%) of ASHw ears and in two (40%) of the ASHb ears, and enlarged vestibular aqueduct was seen in three (50%) of ASHw ears and in two (40%) of the ASHb ears. Conclusion: Imaging studies identified the etiology in half of the cases of SSD and in one‐third of ASH patients. Our findings strongly support the use of imaging studies in the evaluation of pediatric SSD and ASH. Level of Evidence: 4 Laryngoscope, 130:1007–1010, 2020